2006
DOI: 10.1158/1055-9965.epi-06-0183
|View full text |Cite
|
Sign up to set email alerts
|

A Phase I-II Preoperative Biomarker Trial of Fenretinide in Ascitic Ovarian Cancer

Abstract: Purpose: To evaluate study feasibility, toxicity, drug concentrations, and activity of escalating doses of the synthetic retinoid fenretinide [N-(4-hydroxyphenyl)retinamide (4-HPR)] in ovarian cancer by measuring serum CA125 and cytomorphometric biomarkers in cancer cells collected from ascitic fluid before and after treatment. Methods: Twenty-two naive patients with ascitic ovarian cancer were treated with escalating doses of 4-HPR at 0, 400, 600, and 800 mg/d for 1 to 4 weeks before surgery. Changes in the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 35 publications
0
24
0
Order By: Relevance
“…after 200 mg/day [7,8,[12][13] and it was higher (80-90%) after higher doses (900 mg/m 2 bid) [17][18]. Interestingly, in a trial in which the expected effect of 4-HPR on IGF-I was not observed [13], lack of compliance was excluded because retinol concentrations declined to an extent, that was in the same range previously reported with that dose.…”
Section: Discussionmentioning
confidence: 71%
“…after 200 mg/day [7,8,[12][13] and it was higher (80-90%) after higher doses (900 mg/m 2 bid) [17][18]. Interestingly, in a trial in which the expected effect of 4-HPR on IGF-I was not observed [13], lack of compliance was excluded because retinol concentrations declined to an extent, that was in the same range previously reported with that dose.…”
Section: Discussionmentioning
confidence: 71%
“…Among the investigated patients, two controls and four treated, PLAB was upmodulated in 2/4 treated patients. The phase I-II trial was run in patients with ascitic ovarian cancer to evaluate toxicity, drug concentrations and markers of activity of escalating doses of 4-HPR (Colombo et al, 2006). 4-HPR doses up to 800 mg/day did not show any noticeable biological activity measured as changes in Ki-67 expression, cytomorphometric parameters and serum CA125.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with newly diagnosed ascitic ovarian cancer were recruited in a phase I/II study (Colombo et al, 2006). Twentytwo patients were treated with escalating doses of 4-HPR at 0, 400, 600 and 800 mg/day for 1-4 weeks before surgery.…”
Section: Subjects and Collection Of Ascitic Ovarian Cancer Cellsmentioning
confidence: 99%
“…SHetA2 can be classified as a Retinoid-Related Molecule (RRM), which exert similar biological effects as retinoids, such as inhibition of cell growth and induction of differentiation, but also exert additional effects, such as apoptosis [59]. Retinoids and RRMs have demonstrated some activity in melanoma and ovarian cancer [5,60,61]. The efficacy and lack of toxicity prompted pre-clinical development of SHetA2 in the US National Cancer Institute (NCI) RAID and RAPID programs, which demonstrated lack toxicity of SHetA2 at doses 50 fold above the dose required to reduce xenograft tumor growth [62][63][64][65].…”
Section: Introductionmentioning
confidence: 99%